A curved-beam based quasi-constant force mechanism supporting large range and force-sensitive robotic manipulation. (June 2022) - Zhang, Qingyi; Yan, Peng; Wang, Haipeng
Abstract: Emerging applications of force-sensitive manipulation with the requirements on grasping safety and efficiency pose significant challenges on the design of compliant constant-force mechanisms with large operating ranges. In this paper, we propose a novel curved-beam based quasi-constant force mechanism fully compatible with the additive manufacturing technology, which is configurable with appropriate arc-elements to achieve quasi-constant force output with a large motion stroke. We develop an analytical model to describe the static deformation behavior of the proposed mechanism and analyze the performance sensitivity of its structural parameters, with which we also propose the optimization formulation and general guidelines for the design of curved-beam based compliant quasi-constant force mechanisms to meet force and displacement requirements. Finite element analysis and experiments are also conducted to comprehensively evaluate the proposed design, demonstrating significant performance improvement over existing results. Highlights: A novel quasi-constant force mechanism based on curved-beam is proposed. An analytical model of multi-sectional curved-beam is derived. Parameter optimization and design guidelines for quasi-constant force mechanism are provided. Experimental validations of the proposed method with demonstrated performance improvement.